Associação do polimorfismo (snps) do gene abcb1 c3435t, com a resposta à quimioterapia neoadjuvante, em mulheres com câncer de mama - Bezerra, Diego de Aragão (2018)
Breast cancer is the second most prevalent malignant neoplasm in women in Brazil, accounting for a large number of malignant neoplasm-related deaths. There are several alternatives used in the breast cancer treatment, being able to be used surgical treatment, radiotherapy and systemic treatment, by cytotoxic chemotherapy, hormonal therapy and biological therapy. When neoadjuvant systemic therapy is indicated, the response to chemotherapy is important for the therapy's success. Some factors can modify this response, such as environmental, genetic and response factors. The MDR gene (ABCB1) encoding the P-glycoprotein, a membrane carrier, responsible for the cellular efflux of a drugs' variety, xenobiotics, cellular metabolites and anticancer agents, structurally independent. Genetic polymorphisms at this site can modify the absorption, accumulation in the tissue and elimination of drugs from the body. Thus, the objective of this study was to evaluate the association between the polymorphism (SNPs) of the ABC34 C3435T gene and the response to neoadjuvant chemotherapy in women with breast cancer in the northern region of Ceará state. A study was conducted with 32 female patients, who used chemotherapy in a neoadjuvant way. The polymorphisms genotyping was done by polymerase chain reaction (PCR) in real-time allelespecific. Statistical analysis was performed using Fisher's exact test or Pearson's Chi-square, using SPSS (Statistical Package for the Social Sciences) software vs20.0. The genotypes found for C3435T polymorphisms were in Hardy-Weinberg equilibrium and their genotypic distributions were respectively CC = 10 (31.1%), CT = 14 (43.8%), TT = 08 (25.0%) being, χ2: 0.86 and P -value> 0.05. The allele frequencies were C = 0.54 and T = 0.46. There were no statistical differences between the genotypes considering the response to neoadjuvant chemotherapy and immunohistochemistry, with the presence of the T allele associated with the worst axillary status response to neoadjuvant chemotherapy. Thus, it was not possible to correlate the C3435T polymorphism presence with the response to neoadjuvant chemotherapy, and it is necessary to carry out new studies in Brazil involving larger cases for the results validation .